Effect of Cooling Rate on The Microstructures And Hardness Of Fe-Ni-Cr Superalloy - Ridhwan, J.; Selamat , M.Z.; Zulfattah, Z. (Penerbit UTeM, 2013)
Fe-Ni-Cr superalloy is a heat resistant material that shows good mechanical strength and resistance to oxidation and corrosion at high temperature.Heat treatment was conducted on Fe-Ni-Cr superalloy to observe its effect on the microstructures and mechanical property namely hardness. Solution treatment were carried out at 900oC, 975oC, 1050oC, and 1125oC followed by two cooling methods i.e quenching and air cool. The samples were analyzed by using materials characterization techniques such as SEM, XRD, and optical microscope. The Fe-Ni-Cr superalloy formed mainly dendritic austenitic structure with Cr23C6 precipitated along the grain boundaries. Increase in solution treatment temperature results in dissolution of chromium carbide, coarser grain, and lower hardness. Different cooling rate after solution treatment shows that fast cooling produces fewer and finer chromium carbide (Cr23C6) precipitates, finer grain, and higher hardness as compared with slow cooling rate. Highest hardness value which is 213.5 Hv was recorded on sample solution treated at 900oC followed by water quenched.